Identification and function of ETH receptor networks in the silkworm Bombyx mori - Ivana Daubnerová (Nature Portfolio, 2021)
Abstract Insect ecdysis triggering hormones (ETHs) released from endocrine Inka cells act on specific neurons in the central nervous system (CNS) to activate the ecdysis sequence. These primary target neurons express distinct splicing variants of ETH receptor (ETHR-A or ETHR-B). Here, we characterized both ETHR subtypes in the moth Bombyx mori in vitro and mapped spatial and temporal distribution of their expression within the CNS and peripheral organs. In the CNS, we detected non-overlapping expression patterns of each receptor isoform which showed dramatic changes during metamorphosis. Most ETHR-A and a few ETHR-B neurons produce multiple neuropeptides which are downstream signals for the initiation or termination of various phases during the ecdysis sequence. We also described novel roles of different neuropeptides during these processes. Careful examination of peripheral organs revealed ETHRs expression in specific cells of the frontal ganglion (FG), corpora allata (CA), H-organ and Malpighian tubules prior to each ecdysis. These data indicate that PETH and ETH are multifunctional hormones that act via ETHR-A and ETHR-B to control various functions during the entire development—the ecdysis sequence and associated behaviors by the CNS and FG, JH synthesis by the CA, and possible activity of the H-organ and Malpighian tubules.